Análise de crescimento da tiririca (Cyperus rotundus L.) - BRIGHENTI, ALEXANDRE MAGNO; SILVA, JOSÉ FRANCISCO DA; SEDIYAMA, TOCIO; SILVEIRA, JOSÉ SEBASTIÃO MACHADO; SEDIYAMA, CARLOS S. (Revista Ceres, 2015)
.